Lake Chad Regional Economic Memorandum : Technical Paper 2. Climate Change, Rural Livelihoods, and Urbanization - Evidence from the Permanent Shrinking of Lake Chad - Jedwab, Remi; Haslop, Federico; Masaki, Takaaki; Rodríguez-Castelán, Carlos (World Bank, Washington, DC, 2021)
There is a vast economic literature studying the effects of climate change on long-run growth, migration, urbanization, and human capital, among several other outcomes. The paper is structured as follows: Section 3.2 dives into some of the physical characteristics of Lake Chad and its water sources. Section 3.3 introduces our novel data. Section 3.4 presents the hypothesis and empirical strategy behind our analysis. Sections 3.5, 3.6 and 3.7 present results on total population, cities and roads, respectively. Finally, section 3.8 concludes.